Clinical feasibility study of an immunotropic drug for treatment of complicated pyodermas - Roman A. Khmel'nitskij; Andrej V. Vislobokov (Belgorod National Research University, 2020)
Introduction: Given a wide range of pathogenesis of the inflammatory process in pyoderma, which involves a variety of links in the immune response, work is underway to find ways to optimize immunocorrection in this pathology. The aim of the study was to evaluate the clinical and economic effectiveness of immunocorrection in severe and chronic forms of pyoderma with drugs from different pharmacological groups. Materials and methods: The data sources were prospective randomized comparative studies of therapy of 107 pyoderma patients aged 18 to 60 years, divided into groups. The patients of the first group additionally used a biologically active additive containing immunoactive molecules and transfer factors (TF) as an immunomodulator; the patients of the second group used glucosaminylmuramildipeptide (GMDP). The clinical effectiveness of regression of inflammatory symptoms on day 10 of treatment was analyzed. Based on the obtained data, the following types of pharmacoeconomical analysis were performed: calculation of the course price, the cost/effectiveness ratio, and the availability coefficient. Results and discussion: The results of the study showed that the number of cured patients was 91.4% in the first group and 97.2% in the second group of patients. The treatment cost when using the drug is by 970 rubles smaller; the cost/effectiveness ratio (CER) per patient was 1.8 higher for a drug containing transfer factors and amounted to 25.9. The calculation of the availability coefficient (AC) revealed a difference in glucosaminylmuramyldipeptide which was 2.1 times smaller. Conclusion: It was found that a drug based on glucosaminylmuramildipeptide is a more effective and cost-effective means of immunocorrection in severe forms of pyoderma. This confirms a faster regression of clinical manifestations of the disease and lower cost/effectiveness ratio and availability coefficient.